Towards English Education Sustainability: A Narrative Inquiry of an Islamic Eco-ELT School in Dompu - Bulan, Arif; Wahyuni, Nur; Ramadhan, Risca Ariska; Karisma, Yana (Register Journal, 2026)
This study aims to accomplish three primary objectives: (1) to identify the key elements that constitute Eco-ELT as a sustainability-oriented pedagogical practice, (2) to describe how school leaders and English teachers construct and enact these practices through their lived and narrative experiences, and (3) to explain the ecological meanings and values that sustain Eco-ELT within a local Islamic school. Drawing on in-depth interviews with the principal and an English teacher, classroom observations, and institutional documents, this study reveals that Eco-ELT is a lived practice shaped by historical, social, and environmental narratives. The findings show that Eco-ELT is rooted in a community initiative, an English course where tuition was paid with waste, which later evolved into a holistic sustainability vision. The principal’s leadership, grounded in reflective learning and community collaboration, led to programs such as SEKAM, English-area policies, and a school-wide environmental culture. Pedagogically, Eco-ELT is implemented through place-based learning, integrating grammar instruction with direct environmental observations in settings such as the Green Lab, composting areas, and thematic gardens. Students act not only as learners but also as ecological agents through roles like “language police” and daily environmental responsibilities. Despite facing challenges related to time constraints, attendance of non-boarding student, and initial skepticism from parents, the school adapts by enhancing communication and showcasing the visible transformation of students. Theoretically, this study positions Eco-ELT as a situated, narrative-driven ecological practice influenced by leadership and place. Empirically, it demonstrates how sustainability-oriented language education can be enacted in resource-constrained yet environmentally committed school contexts.